Distillers grains as alternative feed resources for beef cattle: a comprehensive review - Virgínio Júnior, Gercino Ferreira [UNESP]; Loregian, Kalista Eloisa [UNESP]; Millen, Danilo Domingues [UNESP] (Asian Australasian Association of Animal Production Societies, 2025)
Distillers' grains (DG), including wet (WDG), dried (DDG), and dried with solubles (DDGS), represent valuable coproducts for beef cattle feeding due to their high digestible energy, rumen-undegradable protein, and functional fiber content. This review integrates current knowledge on the nutritional, productive, environmental, and economic implications of DG use in feedlot systems across temperate and tropical regions. At moderate inclusion levels (15-30% of dietary dry matter), DG consistently enhance feed efficiency and reduce feeding costs without compromising growth performance or carcass traits. Their low starch concentration contributes to more stable ruminal fermentation and a lower risk of subacute acidosis compared with high-grain diets. Nevertheless, excessive ether extract and sulfur concentrations may depress fiber digestibility and increase the incidence of metabolic disorders such as polioencephalomalacia when diets are improperly formulated. Environmentally, DG improve resource efficiency by recycling ethanol coproducts and reducing reliance on conventional feed grains; however, their high nitrogen and phosphorus contents can elevate nutrient excretion and potential environmental load if not properly managed. Economically, DG enhance profitability for feedlots located near ethanol plants, though market volatility and transportation costs remain key constraints. Recent advances in coproduct processing and fractionation have mitigated several nutritional limitations, broadening the applicability of DG in precision feeding programs. Future progress will rely on refining nutrient characterization, optimizing phase-specific inclusion, and integrating DG within sustainable beef production frameworks. When strategically incorporated, DG serve as efficient, cost-effective, and environmentally responsible ingredients for modern beef production systems.